2003
DOI: 10.1016/s0969-2126(02)00930-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of DNA Polymerase β with the Mutagenic DNA Lesion 8-Oxodeoxyguanine Reveals Structural Insights into Its Coding Potential

Abstract: Oxidative damage to DNA generates 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG). During DNA replication and repair synthesis, 8-oxodG can pair with cytosine or adenine. The ability to accurately replicate through this lesion depends on the DNA polymerase. We report the first structure of a polymerase with a promutagenic DNA lesion, 8-oxodG, in the confines of its active site. The modified guanine residue is in an anti conformation and forms Watson-Crick hydrogen bonds with an incoming dCTP. To accommodate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
168
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(174 citation statements)
references
References 41 publications
6
168
0
Order By: Relevance
“…4A). Such mutagenic base pairing has been observed for Bacillus fragment (BF pol I) and T7 polymerase (T7) from the high-fidelity A family (4,5), polβ from the X family (26,27), and polκ and Dpo4 from the Y family (2,28) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…4A). Such mutagenic base pairing has been observed for Bacillus fragment (BF pol I) and T7 polymerase (T7) from the high-fidelity A family (4,5), polβ from the X family (26,27), and polκ and Dpo4 from the Y family (2,28) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 60%
“…It has been demonstrated that active site flexibility around the template base allows conformational alternation of 8-oxo-G in DNA polymerases with standard active site dimensions (25). This template flexibility allows the syn 8-oxo-G base to form a potent base pair with mismatched anti dATP, causing A misincorporations by virtually all classes of DNA polymerases (2,4,26) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…However, the ability of purine bases to stack with aromatic rings suggests that dATP or dGTP may simply be stacking with the displaced guanine or with the phenanthrene ring system in the productive complex for purine nucleotide misinsertion. Such a stacking arrangement of purine bases was observed in a structure of a ternary complex of Pol ␤ with a templating 8-oxodG that had been incubated with dATP (46). In another possible mechanism, the syn-conformation of the adducted deoxyguanosine could serve as a template for purine nucleotide misinsertion.…”
Section: Discussionmentioning
confidence: 92%
“…UDG and APE are relatively small enzymes that bend the helix axis of DNA Ϸ20°and 35°, respectively, on binding (36,37). This distortion is considerably less than that of a nicked DNA molecule bound to pol ␤, which causes a bend of Ϸ90° (38,39). Moreover, the catalytic activity of the V(D)J recombinase enzymes recombination-activating gene (RAG) 1 and RAG2 was tested on a nucleosome substrate, in combination with the nonhistone proteins HMG1 and HMG2 (7).…”
Section: Discussionmentioning
confidence: 99%